2018
DOI: 10.20944/preprints201811.0387.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Are Soybean Yields Getting a Free Ride From Climate Change? Evidence From Argentine Time Series

Abstract: Soybean yields are often indicated as an interesting case of climate change mitigation due to the beneficial effects of CO2 fertilization. In this paper we econometrically study this effect using a time series model of yields in a multivariate framework for a main producer and exporter of this commodity, Argentina. We have to deal with the upward behavior of soybean yields trying to identify which variables are the long-run determinants responsible of its observed trend. With this aim we adopt a partial system… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…Our results indicate a direct relationship between water deficit or variable temperatures and the achievable yield of the soybean (Felix) variety. The amount of rainfall from the sowing to blooming period, together with high temperatures had the greatest effect on the level of the soybean production, which was in accordance with the results obtained by [37,38], who found that there were negative climate effects on soybean yield, due to periods of drought and high temperatures during the growing season. The authors of [39] showed that there was a clear positive response of soybean yield to the increased mean daily maximum temperature, during seed filling, which ranged from 20 to 24 • C. The effects of temperature on soybean yield are complex, in which yield is determined by the growth and partition as well as phenological development and all these responses have different ranges of optimal temperatures.…”
Section: Climate and Soybean Yieldsupporting
confidence: 90%
“…Our results indicate a direct relationship between water deficit or variable temperatures and the achievable yield of the soybean (Felix) variety. The amount of rainfall from the sowing to blooming period, together with high temperatures had the greatest effect on the level of the soybean production, which was in accordance with the results obtained by [37,38], who found that there were negative climate effects on soybean yield, due to periods of drought and high temperatures during the growing season. The authors of [39] showed that there was a clear positive response of soybean yield to the increased mean daily maximum temperature, during seed filling, which ranged from 20 to 24 • C. The effects of temperature on soybean yield are complex, in which yield is determined by the growth and partition as well as phenological development and all these responses have different ranges of optimal temperatures.…”
Section: Climate and Soybean Yieldsupporting
confidence: 90%
“…However, as a long run concept, weak exogeneity can give dierent results from those obtained analysis Granger causality. Ahumada and Cornejo (2018) found that all variables adjust to deviations from the long-run equilibria. This nding implies that climate variables are not weak exogenous which indicates that a system approach should be followed instead of estimating a single equation model.…”
Section: Exogeneitymentioning
confidence: 98%
“…Using daily data of maximum temperature from 54 meteorological stations of the Argentine soybean production area from 1973 to 2015, Ahumada and Cornejo (2018) constructed dierent variables that measure the number of days in a year, during the growing phase of the crop (from December to April) in which the temperature exceeded a threshold of 28…”
Section: Non-linearitiesmentioning
confidence: 99%
See 2 more Smart Citations